Law Enforcement in Medical Malpractice Cases in The Protection of Doctors’ Rights: Case Study Tonsil Surgery Causing Brainstem Death in a Child Patient - Putri, Anggya Nurmala; Sigalingging, Bagas Pratama; Yusnita, Ummi (Justice Voice, 2023)
This study aims to determine the regulations related to the protection of the professional rights of a doctor who is often suspected of committing medical malpractice in carrying out health services. In this study, the author analyzes the rules of malpractice based on positive law in Indonesia, then the author analyzes the liability carried out by the doctor’s profession in suspected malpractice in this study the author takes a case study related to tonsil surgery which caused BA’s child patient to experience brain death at the Kartika Husada, Bekasi Hospital. The method used by the author in this research uses normative or dogmatic research methods, which use documents laws, and regulations related to the issues studied and secondary data sources in the form of books and related journals. The results of the research in this case study conclude that there is no single rule that protects the rights of a doctor who is accused of committing malpractice, neglecting these rules only protects the interests of the patient, then the responsibility for the accusation of malpractice must go through the process of proof first, by the provisions of the elements of malpractice both in terms of criminal and civil law, and based on the case study that has been researched by the author, it is concluded that the efforts in dispute resolution made by the family of BA’s child patient who has died, are appropriate with the family by withdrawing the police report and carrying out peaceful efforts in the form of mediation with the hospital.